(untitled) (Horizontes de Enfermería, 2018)
Automation is a problem that has been called for many years, and as an inconvenience in the work of health at local, national and global level is an object of a comprehensive analysis in the present research. The objective of this research was to know the prevalence of self - medication in patients treated at the Hospital San Gabriel Basic in the period 2016-July 2017, in addition to encouraging patients to evoke this practice that can be very serious. 1400 patients were attended in the emergency area and 800 in the hospitalization area, the prevalence was 40.8% of patients who incurred self - medication before going to the health facility to be attended by a professional, the drugs most consumed were Analgesics, Antigripales and antibiotics in some cases to antibiotics only managed at the hospital level but are dispensed by pharmacies without discrimination or control, among the main sources of information that lead to self - medication are television, the internet and person - to - person talk. The results of this research report alarming numbers of self - medication since almost half of patients attended at this health facility are self - medicated prior to medical care, taking into account that a health care home is attended by a varied number of patients with diffe rent ethnicity and nationality. Therefore it is necessary to create urgent health and control policies to avoid that the practice of self - medication diminishes significantly and / or disappear from our population for the benefit not only of Ecuadorian Health but also of World Health.